Is the Weigl Colour-Form Sorting Test Specific to Frontal Lobe Damage?. (10th February 2021) - Mole, Joseph; Dore, Charlotte; Xu, Tianbo; Shallice, Tim; Chan, Edgar; Cipolotti, Lisa
Abstract: Objective: The Weigl Colour-Form Sorting Test is a brief, widely used test of executive function. So far, it is unknown whether this test is specific to frontal lobe damage. Our aim was to investigate Weigl performance in patients with focal, unilateral, left or right, frontal, or non-frontal lesions. Method: We retrospectively analysed data from patients with focal, unilateral, left or right, frontal ( n = 37), or non-frontal ( n = 46) lesions who had completed the Weigl. Pass/failure (two correct solutions/less than two correct solutions) and errors were analysed. Results: A greater proportion of frontal patients failed the Weigl than non-frontal patients, which was highly significant ( p < 0.001). In patients who failed the test, a significantly greater proportion of frontal patients provided the same solution twice. No significant differences in Weigl performance were found between patients with left versus right hemisphere lesions or left versus right frontal lesions. There was no significant correlation between performance on the Weigl and tests tapping fluid intelligence. Conclusions: The Weigl is specific to frontal lobe lesions and not underpinned by fluid intelligence. Both pass/failure on this test and error types are informative. Hence, the Weigl is suitable for assessing frontal lobe dysfunction.